Kelestarian dalam perjanjian alam sekitar pelbagai hala: sudut pandangan Malaysia - Muhammad Rizal Razman,; Jamaluddin Md. Jahi, (Environmental Management Society, Malaysia, 2010)
One of the successful Multilateral Environmental Agreements (MEAs) is Montreal Protocol. Montreal Protocol managed to seek international environmental cooperation among almost all of the states in the world. All of these states have already agreed to ratify the Montreal Protocol. The Montreal Protocol has been enacted for the protection of the ozone layer to control world emissions of substances that deplete the ozone layer in order to protect global human habitat and environment. Therefore, the primary purpose of this study is to explain on Malaysian experiences in the process of the negotiations of the Montreal Protocol which concerned with the protection on human habitat and environment within the framework of sustainability science. Sustainability science is very essential in determining answers from the questions, which are based on multidisciplinary and trans-disciplinary characteristics. In addition sustainability science is also based on a firm understanding of the fundamental characters of complex interactions and interdependencies between natural, human, and social systems. Meanwhile, this study uses a qualitative approach by interviewing the key persons that represented Malaysia in the process of the negotiations towards the formation and acceptance of the Montreal Protocol based on Malaysian experinces within the framework of sustainability science